2019
DOI: 10.1136/bmjgh-2019-001590
|View full text |Cite
|
Sign up to set email alerts
|

Quick fix for care, productivity, hygiene and inequality: reframing the entrenched problem of antibiotic overuse

Abstract: Antimicrobial resistance (AMR) is a major challenge of our time. A key global objective is to reduce antibiotic use (ABU), in order to reduce resistance caused by antimicrobial pressure. This is often set as a ‘behaviour change’ issue, locating intervention efforts in the knowledge and attitudes of individual prescribers and users of medicines. Such approaches have had limited impact and fall short of addressing wider drivers of antibiotic use. To address the magnitude of antibiotic overuse requires a wider le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(105 citation statements)
references
References 40 publications
(31 reference statements)
3
102
0
Order By: Relevance
“…Healthcare seeking is embedded in social, economic, political and institutional structures and belief systems. Individuals in resource-poor settings have limited capacity to make the same evidence-based choices that are available in more advantaged populations [ 13 , 17 , 41 ]. ‘Structural violence’ in government facilities inhibits access to the public sector for antibiotic medicines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Healthcare seeking is embedded in social, economic, political and institutional structures and belief systems. Individuals in resource-poor settings have limited capacity to make the same evidence-based choices that are available in more advantaged populations [ 13 , 17 , 41 ]. ‘Structural violence’ in government facilities inhibits access to the public sector for antibiotic medicines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…References to the informal sector, whether in housing, the labour market or healthcare are often made in a normative context, imposing unfair judgment and discrimination on disadvantaged and marginalised populations for whom these services offer the most affordable and suitable option [ 46 ]. In this study, informants reported self-medicating with antibiotics because they believed, in good faith, that these medicines would alleviate symptoms and lead to recovery [ 17 ]. Our findings illustrate how the acceptability of village pharmacies as providers of antibiotic medicines is embedded within the social and cultural fabric.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…105 However, in the main, present needs have overridden future-focused stewardship concerns. While there is no reason not to use antibiotics to save and improve lives, they have often been used as a 'quick fix' 106 to symptomatically control rather than eliminate underlying drivers of infection in human, animal health and plant production systems. The tendency to see antibiotics as 'quick fixes' has helped drive AMR and often distracted from investment in more sustainable forms of infection prevention like effective and affordable health, Water, Sanitation and Hygiene (WASH), and Infection Prevention Control (IPC) systems (see also Inequality below).…”
Section: Prioritisationmentioning
confidence: 99%